2022
DOI: 10.1136/bmjopen-2021-053642
|View full text |Cite
|
Sign up to set email alerts
|

Impact of virtual care on health-related quality of life in children with diabetes mellitus: a systematic review protocol

Abstract: IntroductionDiabetes mellitus is the most common endocrine disorder in children, and the prevalence of paediatric type 1 and type 2 diabetes continue to rise globally. Diabetes clinical care programs pivoted to virtual care with the COVID-19 pandemic-driven social distancing measures. Yet, the impact of virtual care on health-related quality of life in children living with diabetes remains unclear. This protocol reports on the methods that will be implemented to conduct a systematic review to assess the health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Of 175 international systematic reviews identified in PubMed (date of search: 9 December 2022), 10 potentially relevant reviews described impact on glycaemic control,17–20 diabetic ketoacidosis21 and interventions to recover or sustain diabetes or hypertension care 22–26. Overall, improvements in glycaemic control were seen in high-income countries during the pandemic, likely reflecting a high motivation for diabetes self-management due to associations with COVID-19 outcomes, supportive care through teleconsultations, and easier meal-planning, improved sleep habits and reduced access to fast food when staying at home during movement restrictions 17 18.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Of 175 international systematic reviews identified in PubMed (date of search: 9 December 2022), 10 potentially relevant reviews described impact on glycaemic control,17–20 diabetic ketoacidosis21 and interventions to recover or sustain diabetes or hypertension care 22–26. Overall, improvements in glycaemic control were seen in high-income countries during the pandemic, likely reflecting a high motivation for diabetes self-management due to associations with COVID-19 outcomes, supportive care through teleconsultations, and easier meal-planning, improved sleep habits and reduced access to fast food when staying at home during movement restrictions 17 18.…”
Section: Introductionmentioning
confidence: 99%
“…Four systematic reviews reported on interventions to sustain diabetes or hypertension care during the COVID-19 pandemic internationally,22 23 25 26 and one review protocol was identified 24. Telehealth and home visits were mentioned as modalities to manage diabetic foot conditions 25.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations